Prolidase is a critical enzyme for complete gliadin digestion in Tenebrio molitor larvae. Issue 4 (29th June 2017) - Tereshchenkova, Valeriia F.; Goptar, Irina A.; Zhuzhikov, Dmitry P.; Belozersky, Mikhail A.; Dunaevsky, Yakov E.; Oppert, Brenda; Filippova, Irina Yu.; Elpidina, Elena N.
Abstract: Prolidase is a proline‐specific metallopeptidase that cleaves imidodipeptides with C‐terminal Pro residue. Prolidase was purified and characterized from the Tenebrio molitor larval midgut. The enzyme was localized in the soluble fraction of posterior midgut tissues, corresponding to a predicted cytoplasmic localization of prolidase according to the structure of the mRNA transcript. Expression of genes encoding prolidase and the major digestive proline‐specific peptidase (PSP)—dipeptidyl peptidase 4—were similar. The pH optimum of T. molitor prolidase was 7.5, and the enzyme was inhibited by Z‐Pro, indicating that it belongs to type I prolidases. In mammals, prolidase is particularly important in the catabolism of a proline‐rich protein—collagen. We propose that T. molitor larval prolidase is a critical enzyme for the final stages of digestion of dietary proline‐rich gliadins, providing hydrolysis of imidodipeptides in the cytoplasm of midgut epithelial cells. We propose that the products of hydrolysis are absorbed from the luminal contents by peptide transporters, which we have annotated in the T. molitor larval gut transcriptome. The origin of prolidase substrates in the insect midgut is discussed in the context of overall success of grain feeding insects.